XVI a. pab.-XVII a. Vilniaus spaustuvių knygų grafika (Kelios pastabos Vilniaus knygų grafikos meniškumo klausimu) - Liškevičienė, Jolita (Knygotyra, 1998)
The printing activities flourished in Vilnius from the end of the sixteenth century. We may talk about two periods with distinctive features in book illustration in relation to printed book graphics: 1) the end of the sixteenth century to the 1640s; 2) the 1640s to the end of the seventeenth century. The books in the printing houses of Vilnius were illustrated very modestly. The initials, headpieces, tailpieces, and ornamented page frames were the main decorations used by the printing houses in Vilnius. These elements were repeated in publications issued by different religious confessions because it was common to borrow or rent the same engraved plates at the end of the sixteenth century. The first books published in Vilnius had no uniform style because the printer was responsible for the appearance of a book in addition to other duties. Besides two inherited traditions of book illustration (the Eastern one that used two-colored printing inherited from Russian manuscripts; the Western one coming from German book decoration), a third, new and modern decoration with emblems emerged during the first period. The use of emblems introduced symbolic thinking and a tripartite composition scheme that ruled over the ornamented space of the book. During this period, several occasional publications were decorated with emblems or ornamented according to the rules of emblematic composition. Most of these engravings were done on wood, had a uniform style, and belonged to one professional engraver who worked in Vilnius. At the beginning of the seventeenth century, copper engravings became widespread: one known collection of emblems was decorated by cartographer Tom Makovski, who had served in the Radvila court. That book, Divi tutelaris..., was dedicated to St. Kazimieras and consisted of 24 emblems (copper engravings) with lemmas expressing the virtue of the saint in one word, and a poem of 12 lines. During this period, one could find not only provincial elements but also features of professional book decoration. The coat of arms was one of the most popular elements found in the books of the sixteenth and seventeenth centuries. It was meant to honor the dedicatee and was usually printed in a prominent place—on the reverse of the title page. At the beginning, arms were represented according to very strict rules of composition. Later, the arms became part of a complex illustration: they were freely composed with other emblems, allegorical images, or a portrait into a unified composition. During the seventeenth century, the tradition of title-page decoration flourished in Vilnius. Sometimes the whole content of the book was symbolically represented in the title-page decoration. The main means acquired in the graphical experience of Vilnius illustrators were used: emblematic elements were joined with coats of arms, allegorical figures held shields, and portraits were surrounded by intricate garlands full of different attributes. The composition of the title page was saturated with decorative elements and became the main artistic representation in a book. The professional level of book graphics in Vilnius during this period was very varied: there were both highly professional and very weak engravings of poor taste.